Riproximin Exhibits Diversity in Sugar Binding, and Modulates some Metastasis-Related Proteins with Lectin like Properties in Pancreatic Ductal Adenocarcinoma - Sagini, Micah N.; Klika, Karel D.; Orry, Andrew; Zepp, Michael; Mutiso, Joshua; Berger, Martin R. (Frontiers in Pharmacology, 2020)
Riproximin (Rpx) is a type II ribosome-inactivating protein with specific anti-proliferative activity. It was purified from Ximenia americana by affinity chromatography using a resin coupled with lactosyl residues. The same technique facilitated isolation of proteins with lectin-like properties from human Suit2-007 pancreatic cancer cells, which were termed lactosyl-sepharose binding proteins (LSBPs). The role of these 1,194 proteins in cancer progression was investigated at mRNA level using chip array data of Suit2-007 cells re-isolated from nude rats. These data compared significant mRNA expression changes when relating primary (pancreas) and metastatic (liver) sites following orthotopic and intraportal implantation of PDAC cells, respectively. The affinity of Rpx to 13 simple sugar structures was modeled by docking experiments, the ranking of which was principally confirmed by NMR-spectroscopy. In addition, Rpx and LSBPs were evaluated for anti-proliferative activity and their cellular uptake was assessed by fluorescence microscopy. From 13 monosaccharides evaluated, open-chain rhamnose, β-D-galactose, and α-L-galactopyranose showed the highest affinities for site 1 of Rpx’s B-chain. NMR evaluation yielded a similar ranking, as galactose was among the best binders. Both, Rpx and LSBPs reduced cell proliferation in vitro, but their anti-proliferative effects were decreased by 15-20% in the presence of galactose. The program ‘Ingenuity Pathway Analysis’ identified 2,415 genes showing significantly modulated mRNA expression following exposure of Suit2-007 cells to Rpx in vitro. These genes were then matched to those 1,639 genes, which were significantly modulated in the rat model when comparing primary and metastatic growth of Suit2-007 cells. In this overlap analysis, LSBP genes were considered separately. The potential suitability of Rpx for treating metastatic Suit2-007 PDAC cells was reflected by those genes, which were modulated by Rpx in a way opposite to that observed in cancer progression. Remarkably, these were 14% of all genes modulated during cancer progression, but 71% of the respective LSBP gene subgroup. Based on these findings, we predict that Rpx has the potential to treat PDAC metastasis by modulating genes involved in metastatic progression, especially by targeting LSBPs.